POVERTY OF ELdDERLY WORKERS IN SOUTH KOREA (International journal of artificial intelligence, 2025)
as a result of population aging and economic changes, poverty rates among the elderly, especially those in the workforce, are increasing. Although South Korea has a social protection system for the elderly, many older workers struggle to meet their needs. The article examines the support systems for older workers, their economic situation, social protection programs, and labor market opportunities.